013 Free-breathing MOCO LGE leads to better image quality and faster scanning times in clinical practice. (3rd April 2017) - Lobascio, Ilaria; Captur, Gabriella; Culotta, Veronica; Boubertakh, Redha; Eke, Andras; Xue, Hui; Manisty, Charlotte; Kellman, Peter; Moon, James C
Abstract : Objectives: Late gadolinium enhancement (LGE) sequences have evolved. Free-breathing, motion-corrected LGE (MOCO-LGE) 1, 2 has several potential advantages over breath held LGE (bh-LGE) 3 including minimal user input for the LGE short axis (SA) stack and no need for breath-holds. We hypothesised that the use of MOCO-LGE would be faster, cheaper and easier for clinical scanning, increasing throughput. Methods: 200 consecutive clinical patients underwent bh-LGE or MOCO-LGE at 1.5T. Image quality (Figure 1 ), scan time, patient throughput (change-over time) and reader confidence were compared. LGE image quality was evaluated qualitatively (adaption of previously reported method) 4 and quantitatively (assessing image texture heterogenity using grayscale lacunarity, λ). Results: MOCO-LGE image quality was better than bh-LGE qualitatively (lower score better: 0.56±1.2 vs 1.93±0.83, p<0.0001) especially in clinically vulnerable patients eg. atrial fibrillation, poor breath-holding, low ejection fraction (0.59 vs 3.05, p=0.0001). Excellent image quality (score=0) was also more common (78% vs 27%, p<0.0001). Quantitative image quality was superior with MOCO-LGE (lower score better: blood pool lambda bh-LGE 0.38±0.11 vs MOCO-LGE 0.28±0.08, p<0.0001). MOCO-LGE led to greater diagnostic confidence (blinded review: basic analytic, retained diagnostic and "Omary" correction methods, respectively p=0.005; p=0.018, p<0.001). Although patient change-over time did not differ significantly between scan protocols, total LGE imaging time was 1.6 times shorter with MOCO-LGE compared to bh-LGE (5.23 vs 8.84 minutes, p<0.0001). Conclusion: MOCO-LGE is superior to bh-LGE in a clinical service, with better image quality, easier interpretation and faster scanning times. References: . Maria JLedesma-Carbayo, Peter Kellman, Andrew EArai, et al. Motion corrected free-breathing delayed-enhancement imaging of myocardial infarction using nonrigid registration . JMRI Published Online First : 20 Jul 2007. 2. Peter Kellman, Andrew EArai. Cardiac imaging techniques for physicians: Late enhancement. JMRI Published Online First : 17 Aug 2012.3. Piehler KM, Wong TC, Puntil KS, et al. Free-breathing, motion-corrected late gadolinium enhancement is robust and extends risk stratification to vulnerable patients. Circ Cardiovasc Imaging 2013;6 (3):423-32.4. Vincenzo Klinke, Stefano Muzzarelli, Nathalie Lauriers, et al. Quality assessment of cardiovascular magnetic resonance in the setting of the European CMR registry: description and validation of standardized criteria. J Cardiovasc Magn Reson 2013;15 :55.